2020
DOI: 10.1519/jsc.0000000000002814
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve Change-of-Direction Speed in Junior Team Sport Athletes—Horizontal, Vertical, Maximal, or Explosive Strength Training?

Abstract: Keller, S, Koob, A, Corak, D, von Schöning, V, and Born, DP. How to improve change-of-direction speed in junior team sport athletes-Horizontal, vertical, maximal, or explosive strength training? J Strength Cond Res XX(X): 000-000, 2018-The purpose of the study was to compare the effects of 4 different training methods on change-of-direction (COD) speed in junior team sport athletes. Specifically, we investigated whether horizontal load training incorporating lateral acceleration and deceleration would induce s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 34 publications
0
26
0
3
Order By: Relevance
“…Earlier training studies have shown that implementing some of these plyometric exercises in training increased COD performance [ 34 ]. The skate jump had the highest associations with the different COD, while only similar exercises performed laterally are supplemented in earlier training interventions [ 16 , 68 , 69 ], it would be interesting to investigate the isolated effect of this exercise in future training studies and how it effects COD performance. Furthermore, the plyometric exercises displayed a greater similarity in muscle activation in the hamstring muscles, adductor longus, gastrocnemius, gluteus medius and a greater association with COD performance compared to the strength exercises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier training studies have shown that implementing some of these plyometric exercises in training increased COD performance [ 34 ]. The skate jump had the highest associations with the different COD, while only similar exercises performed laterally are supplemented in earlier training interventions [ 16 , 68 , 69 ], it would be interesting to investigate the isolated effect of this exercise in future training studies and how it effects COD performance. Furthermore, the plyometric exercises displayed a greater similarity in muscle activation in the hamstring muscles, adductor longus, gastrocnemius, gluteus medius and a greater association with COD performance compared to the strength exercises.…”
Section: Discussionmentioning
confidence: 99%
“…As such, strength-and plyometric-training interventions are often utilized to try to improve COD performance, implementing different squat variations performed bilaterally and unilaterally, with movements in both the vertical and lateral direction [16][17][18][19][20][21][22]. Plyometric training often includes drop jumps [23][24][25][26][27] and/or countermovement jumps [28][29][30][31][32][33] with variations in ground reaction forces produced.…”
Section: Introductionmentioning
confidence: 99%
“…Jumping ability is crucial for successful performance of several team sports’ fundamental motor skills, in addition to being the most widely used task to improve and indirectly measure lower limb power in multidirectional sports [ 12 , 13 ]. Although some authors have suggested that jumping ability development may be influenced by sport-specific training adaptations in team sports young athletes [ 14 ], evidence has shown no differences between soccer and basketball players for vertical bilateral jump performance, suggesting no specific training adaptation required for these athletes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, more knowledge of how to improve the COD performance is of great importance to sport and conditioning coaches. Several studies have utilized strength training [14][15][16][17][18][19][20], specific COD drills [21][22][23][24][25], plyometric training [26][27][28][29] and a combination of these different training forms [30][31][32][33][34][35] to the physical aspect of COD performance [9].…”
Section: Introductionmentioning
confidence: 99%